Comparison of Quality of Life between Fixation and Arthroplasty in Intertrochanteric Fracture of Femur in Elderly Patients - Pornmeechai, MD, Yodsawee; Tanpowpong, MD, Thanathep (Journal of Southeast Asian Orthopaedics, 2022)
Background: Standard treatment for intertrochanteric fracture is internal fixation. Arthroplasty is an alternative treatment for these fractures in some specific conditions. Apart from hip functional score, health-related quality of life (HRQoL) is one of the interesting domains that can reflect the outcome of the treatment. However there are many conditions affecting HRQoL especially in the elderly patients. Objective: To evaluate the HRQoL of the patients between treatment of intertrochanteric fracture in elderly with fixation and arthroplasty. Materials and Methods: In this retrospective study, 143 intertrochanteric fracture patients who were treated during 2001-2015 were included. The patients were divided into 2 groups; 82 patients in fixation group and 61 patients in arthroplasty group. HRQoL between 2 groups were compared by EuroQol-5D-5L(EQ-5D-5L) index score at 3, 6 and 12 months postoperatively. Results: The mean of EQ-5D-5L index score was significantly better in arthroplasty group than fixation group at 3 months (0.8 vs 0.6)(P < 0.05) and 6 months (0.91 vs 0.78)(P < 0.05) postoperatively. However, there was no significant difference at 12 months (0.94 vs 0.87)(P = 0.15). Conclusion: Arthroplasty in intertrochanteric fracture in elderly might give better quality of life than fixation in the early postoperative period.